2013
DOI: 10.1530/erc-13-0234
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 immunolocalization in human breast cancer patients as a prognostic factor

Abstract: Nuclear factor erythroid 2-related factor 2 (NRF2 (NFE2L2)) is an important transcriptional activator involved in the cellular defense mechanisms against electrophilic and oxidative stress. Recent studies have demonstrated that the expression of NRF2 protein is upregulated in several human malignancies and is associated with worse prognosis in these patients. However, the pathological and clinical significance of NRF2 has remained largely unknown in breast cancer patients. Therefore, in this study, we immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…Glioma patients with high Nrf2 expression had significantly shorter OS and DFS than glioma patients with low Nrf2 expression. Our results are consistent with the results reported in previous studies, in which high Nrf2 expression indicated the poor outcomes in malignant tumors [8][9][10]. In addition, high Nrf2 expression correlates with high tumor grade and indicates high degree of malignancy in gliomas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Glioma patients with high Nrf2 expression had significantly shorter OS and DFS than glioma patients with low Nrf2 expression. Our results are consistent with the results reported in previous studies, in which high Nrf2 expression indicated the poor outcomes in malignant tumors [8][9][10]. In addition, high Nrf2 expression correlates with high tumor grade and indicates high degree of malignancy in gliomas.…”
Section: Discussionsupporting
confidence: 93%
“…However, the protective effects of Nrf2 cannot discriminate the normal cells from cancer cells [7]. It has been demonstrated that high levels of Nrf2 promote cancer cell survival; contribute to chemoresistance; and associate with poor prognosis in a variety of malignant tumors, such as lung cancer, pancreatic cancer, and breast cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the abnormal incidence of mutations in the NFE2L2/KEAP1/CUL3 pathway and high expression of NFE2L2 in various cancers, in agreement with our results (9,(18)(19)(20)(21). Nevertheless, there are some controversial views about the expression of KEAP1 in tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, the confluent cell layer was scratched using a sterile plastic P‐200 pipette tip after transfection and incubated for 48  h. The migration area was evaluated using the MultiGauge v3.1 Software (Fuji Photo Film, Tokyo, Japan), and the relative migration area was then calculated as the ratio of that in the control cells transfected with negative control (NC) in this study 16.…”
Section: Methodsmentioning
confidence: 99%